Investigating Willingness to Invest in Renewable Energy to Achieve Energy Targets and Lower Carbon Emissions - Karasmanaki, Evangelia; Galatsidas, Spyridon; Ioannou, Konstantinos; Tsantopoulos, Georgios (Atmosphere, 2023)
There is a keen interest in renewable energy sources (RES) as a key aspect of reducing the emissions of greenhouse gases (GHG). Supporting policies have facilitated citizen investments in renewable energy, as such investments can make a substantial contribution to emissions reduction. The problem, however, is that the factors affecting citizen willingness- to invest in renewable energy are still uncertain and tend to constantly change, highlighting the need to perform studies on the subject more frequently. As citizen investments in RES can contribute to emissions reduction, the aim of this study is to understand the factors that affect the willingness of citizens to invest in renewable energy. Using simple random sampling, a representative sample of 1536 citizens in an EU country was administered structured questionnaires, and the results were analyzed using logistic regression. It was shown that willingness to invest is affected by both financial and non-financial factors, such as citizens’ agreement with the construction of renewable facilities near their residence, information sources for obtaining information about environmental and energy topics, satisfaction with the media’s coverage of renewable investments, and their occupation. Results from this study raise substantial policy implications and may be used to improve the design of strategies for attracting citizen investments.